Carinicateres merkli gen. et sp. nov. from Thailand, with notes on identification of two lophocateride beetles used in recent molecular phylogenies (Cleroidea, Lophocateridae) - Kolibáč, Jiří (Zootaxa, 2021)
Carinicateres merkli gen. et sp. nov. of Lophocateridae from eastern Thailand is described. The monotypic genus is distinct in its unique synapomorphies, namely the tarsal formula 4-4-4, elytron with 2 complete and 3 incomplete carinae, antenna 10-segmented with 2-segmented club. The emarginate frontoclypeal suture, mandible with mola, prementum divided into two parts, cranium dorsally with large impressions, each with seta in centre, crenulate lateral margins of pronotum, and distinct dorsal vestiture are shared with lophocateride genera Indopeltis Crowson and Trichocateres Kolibáč. Two specimens affiliated to Lophocateres Olliff and recently used in three molecular phylogenetic analyses are unambiguously identified as members of the clade Ancyrona + Neaspis and associated with Neaspis Pascoe.